Lomentospora prolificans vertebral osteomyelitis with spinal epidural abscess in an immunocompetent woman: Case report and literature review - Walaiporn Wangchinda (2019)
© 2018 The Authors Lomentospora prolificans is a rare cause of vertebral osteomyelitis. We report a case of L. prolificans thoracic vertebral osteomyelitis with spinal epidural abscess in a patient without apparent immunodeficiency. Clinical manifestations and radiographic findings could not distinguish from other etiologic agents. Treatment is also challenging because L. prolificans is usually resistant to antifungal agents. The patient underwent surgical debridement and has been receiving a prolonged combination of antifungal therapy to prevent an infection relapse.